Lacan's Concept of Desire Through Peter Turner and Gloria Grahame Age-Gap Relationship in Stars Don't Die in Liverpool (2017) - Putri Angelika Nur Maghfiroh (Universitas Negeri Surabaya, 2026)
This study explores the portrayal of desire in Stars Don’t Die in Liverpool (2017), focusing on how the main character’s desire is depicted and how it is influenced by the age-gap relationship between Peter Turner and Gloria Grahame. Using Jacques Lacan’s psychoanalytic theory, particularly the concepts of lack, objet petit a, and the three orders such as, The Imaginary, The Symbolic, And The Real, this research investigates the unconscious forces shaping the characters’ emotional experiences and interpersonal dynamics. This study applies close analysis of selected film scenes to reveal how Peter Turner and Gloria Grahame’s desires emerge and evolve. By analyzing cinematic elements such as dialogue, character behavior, and visual symbolism, the study demonstrates how the age difference between the two characters adds complexity to their longing, illusions, and emotional breakdowns. The findings suggest that their desires are not merely romantic, but psychologically constructed within a system of loss, idealization, and social constraints.